1783 Mass. Acts 37 - (:unkn) unknown (My University, 1783)
§ 2: Prohibited the possession of any "fire arms," and among other devices, loaded with any gun powder. Punishable by forfeiture and sale at public auction.
Keywords: POSSESSION